Potret Hutan Adat di Desa Ewiri Kecamatan Leksula, Kabupaten Buru Selatan - iskar, iskar; Silaya, Th. M.; Teslatu, Inka (MAKILA, 2021)
The indigenous people of Ewiri Village are part of the ulayat (petuanan) Massarette in South Buru, which has local wisdom in Sasi (sihit), Enhamat, Tane Mehet, indigenous forests, Karamat/ Pamali, and Dusun. Indigenous peoples in Ewiri Village still have the structure and form of indigenous peoples, indigenous institutions, customary institutions, customary jurisdictions, customary law sanctions, and a very high dependence on indigenous forests. This study examines the management of customary forests in Ewiri Village, Leksula District, South Buru Regency. The research method used is descriptive research used to describe a human group's status or a particular data. Data is collected through interviews of respondents and key informants. The results showed that the management of indigenous forests in Ewiri Village has a relatively high dependence on forests. The community still maintains the customs, traditions of their ancestors, local wisdom, local knowledge, and other land-use practices. Customary Forest Ownership Rights are regulated based on the distribution of houses or soa indigenous peoples of Ewiri Village. The existing margas are Selsily Clan (Gefua), Solissa Clan (Mual), Lesnussa Clan (Masbait), Nustelu Clan (Marmau) and Behuku (Humboti). The pattern of utilization and management of customary forests by the indigenous people of Ewiri Village has stages, including land clearing, planting stage, maintenance stage, and harvesting and marketing stage. Forms of customary forest management include natural forests, gardens, and hamlets/air.